Expand undeveloped areas in Islamic economy - New Sarawak, Tribune (New Sarawak Tribune, 2014)
KUALA LUMPUR: Malaysia's Islamic banking and finance is on the right track and now is the time to expand other underdeveloped areas within it to achieve a solid and overall implementation.Islamic Banking and Finance Institute Malaysia (Ibfim) chief operation officer M.Najib Shaharuddin said the focus should be on those areas that are not covered by Bank Negara Malaysia and the Securities Commission.